The anatomy of the caudal zona incerta in rodents and primates - Watson, Charles; Lind, C.; Thomas, M. (Wiley Blackwell Publishing Ltd, 2014)
The caudal zona incerta is the target of a recent modification of established procedures for deep brain stimulation (DBS) for Parkinson's disease and tremor. The caudal zona incerta contains a number of neuronal populations that are distinct in terms of their cytoarchitecture, connections, and pattern of immunomarkers and is located at a position where a number of major tracts converge before turning toward their final destination in the forebrain. However, it is not clear which of the anatomical features of the region are related to its value as a target for DBS. This paper has tried to identify features that distinguish the caudal zona incerta of rodents (mouse and rat) and primates (marmoset, rhesus monkey, and human) from the remainder of the zona incerta. We studied cytoarchitecture, anatomical relationships, the pattern of immunomarkers, and gene expression in both of these areas. We found that the caudal zona incerta has a number of histological and gene expression characteristics that distinguish it from the other subdivisions of the zona incerta. Of particular note are the sparse population of GABA neurons and the small but distinctive population of calbindin neurons. We hope that a clearer appreciation of the anatomy of the region will in the end assist the interpretation of cases in which DBS is used in human patients.